2010
DOI: 10.4330/wjc.v2.i3.43
|View full text |Cite
|
Sign up to set email alerts
|

Stopping the cardiovascular disease continuum: Focus on prevention

Abstract: The cardiovascular disease continuum (CVDC) is a sequence of events, which begins from a host of cardiovascular risk factors that consists of diabetes mellitus, dyslipidemia, hypertension, smoking and visceral obesity. If it is not intervened with early, it inexorably progresses to atherosclerosis, coronary artery disease, myocardial infarction, left ventricular hypertrophy, and left ventricular dilatation, which lead to left ventricular diastolic or systolic dysfunction and eventually endstage heart failure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 71 publications
1
25
0
3
Order By: Relevance
“…In our study, the diagnosis of dyslipidaemia was based on medical history, in which the patient had reported previously elevated blood cholesterol and/or triglyceride concentration, independently of the current blood lipid level, and whether the patient had a history of hypolipidaemic drug use. In this sense, "dyslipidaemia" should be recognized as a long-acting factor, which begins its proatherogenic action in the patient's youth, and, according to the theory of cardiovascular continuum [15,16], has stimulated atherogenesis for many years, rendering insufficient the pharmacological control which had mostly been applied a few years before or on the day of the first endovascular procedure. Such an assumption explains why these patients had worse outcomes for endovascular interventions, probably related to multi-level lesions, including small vessels which are not suitable for any intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the diagnosis of dyslipidaemia was based on medical history, in which the patient had reported previously elevated blood cholesterol and/or triglyceride concentration, independently of the current blood lipid level, and whether the patient had a history of hypolipidaemic drug use. In this sense, "dyslipidaemia" should be recognized as a long-acting factor, which begins its proatherogenic action in the patient's youth, and, according to the theory of cardiovascular continuum [15,16], has stimulated atherogenesis for many years, rendering insufficient the pharmacological control which had mostly been applied a few years before or on the day of the first endovascular procedure. Such an assumption explains why these patients had worse outcomes for endovascular interventions, probably related to multi-level lesions, including small vessels which are not suitable for any intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous observed landmarks on clinical existence of the obesity paradox, one must not disregard that lifestyle modifications and obesity treatment must be the mainstay of therapeutic measures in order to improve outcomes from the cardiovascular disease continuum (25)(26)(27)(28). Treatment of obesity is connected with multiple health benefits, particularly the common risk factors as diabetes, chronic renal disease, hypertension and related to the decrease in total or cardiovascular mortality (17,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that Ang II stimulates the production of MCP-1 and adhesion molecules such as vascular cell adhesion molecule 1 (VCAM-1), intracellular adhesion molecule 1, and (ICAM-1); Ang II also induces the production of matrix metalloproteinase 3 (MMP-3) and matrix metalloproteinase 9 (MMP-9) in macrophage and SMCs; thus Ang II takes part in the pathogenesis of atherosclerosis. 12 ACE2 is a newly discovered member of the RAS. Recent studies have shown that it is a potential therapeutic target for the treatment of atherosclerosis, coronary heart disease and diabetic cardiomyopathy owing to its key role in the formation of vasoprotective peptides, Ang-(1-7), from Ang II.…”
Section: Discussionmentioning
confidence: 99%